Effect of Cabbage Extract on Paracetamol Dissolution: An in-vitro Drug-food Interaction Study - J, Arthi; Bagyalakshmi, J (Archives of Case Reports, 2025)
The interaction between food components and pharmaceutical agents can significantly influence drug dissolution and absorption. The present study aimed to investigate the potential in vitro interaction between cabbage extract and paracetamol using UV spectrophotometry and dissolution testing. A calibration curve for paracetamol was established at 249 nm over the concentration range of 1–8 µg/mL. The curve demonstrated linearity with an R² value of approximately 0.998, confirming that the drug follows Beer–Lambert’s law and validating the method for quantitative estimation. Dissolution testing of a marketed paracetamol tablet was carried out in phosphate buffer at pH 5.8, simulating intestinal conditions. Absorbance values were recorded at 15-minute intervals up to 75 minutes, and the cumulative percentage drug release was calculated. The paracetamol control group exhibited a predictable, linear dissolution profile with a steady increase in absorbance, consistent with expected release behaviour. In contrast, the test group containing cabbage extract, prepared by aqueous maceration and introduced directly into the dissolution medium, demonstrated a non-linear release pattern. Although the absorbance values remained within the standard range (≤ 0.8), noticeable deviations from the control profile were observed, suggesting possible interference. The observed variation may be attributed to phytochemicals present in cabbage, which could alter paracetamol solubility or affect UV spectrophotometric detection. Pharmacokinetic parameters were further evaluated using a one-compartment model, supporting the notion of altered dissolution dynamics in the presence of cabbage extract. Overall, the findings suggest a potential in vitro drug–food interaction between cabbage extract and paracetamol, which may influence the drug’s dissolution and subsequent bioavailability. While the interaction observed is preliminary and limited to in vitro conditions, it highlights the importance of further in vivo pharmacokinetic studies to establish clinical relevance and evaluate whether cabbage consumption could impact the therapeutic efficacy of paracetamol.